Analysis of Expectations Violation Theory of Communication in Tinder Application - Nabila, Nasywa Fildza; Sandy, Fadillah (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2023)
Social media as a means of communication can also be a place for branding, entrepreneurship and marketing. Various apps are very easy to access including online dating apps. The Tinder app is an online dating platform that came into existence in 2012 and has the highest percentage in 2022 compared to other online dating apps. Communication plays an important role in the message exchange that occurs in the Tinder app. The established communication patterns will affect the first impression when meeting in the media. Every human being has expectations of non-verbal messages or behaviors from others. This study aims to analyze the theory of violation of expectations of tinder app users as a communication intermediary to establish relationships. This study used a qualitative descriptive method by conducting structured interviews with active users of the Tinder application. Interviews were conducted to find out the informant’s perspective when using the application. Assumptions arising from the violation of expectations result in the non-occurrence of the same expectations. Based on the results of research, the tinder application is not only to find a partner but also can add relationships both in the world of lectures and in the world of work. Then, two out of three tinder app respondents managed to achieve expectations in using the tinder app.